The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/hepr.12720
|View full text |Cite
|
Sign up to set email alerts
|

L‐carnitine prevents metabolic steatohepatitis in obese diabetic KK‐Ay mice

Abstract: Aim: Pharmacological treatment for metabolic syndromerelated non-alcoholic steatohepatitis has not been established. We investigated the effect of L-carnitine, an essential substance for β-oxidation, on metabolic steatohepatitis in mice. Methods:Male KK-A y mice were fed a high-fat diet (HFD) for 8 weeks, with supplementation of L-carnitine (1.25 mg/mL) in drinking water for the latter 4 weeks.Results: Serum total carnitine levels were decreased following HFD feeding, whereas the levels were reversed almost co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Supplemented mice had significantly higher free carnitine concentrations at time of sacrifice than non-supplemented mice (44.3±5.0 vs. 39.7±4.9 μM, p=0.04). Though a modest difference, other studies supplementing mice with similar doses of LC report variability in the effect on serum/ plasma carnitine levels, ranging between approximately 0.65 to 20 μM higher [32][33][34][35].…”
Section: Carnitine Levelsmentioning
confidence: 89%
“…Supplemented mice had significantly higher free carnitine concentrations at time of sacrifice than non-supplemented mice (44.3±5.0 vs. 39.7±4.9 μM, p=0.04). Though a modest difference, other studies supplementing mice with similar doses of LC report variability in the effect on serum/ plasma carnitine levels, ranging between approximately 0.65 to 20 μM higher [32][33][34][35].…”
Section: Carnitine Levelsmentioning
confidence: 89%
“…In the current study, cotreatment of l ‐Carnitine with hyperuricemia induction ameliorated such carbohydrate metabolic derangement, despite not altering the insulin level compared to the untreated hyperuricemic rats, in line with Samimi et al (). Such protective effects of l ‐Carnitine could be mediated by preventing the rise of serine phosphorylation of IRS‐1, which negatively regulates insulin signaling (Kon et al, ). Also, l ‐Carnitine could increase the efflux of acyl and acetyl groups out of the cells into the plasma, reducing the accumulation of these intermediate products of β‐oxidation (Chapela, Kriguer, Fernández, & Stella, ), improving insulin resistance (Zhang, Keung, Samokhvalov, Wang, & Lopaschuk, ).…”
Section: Discussionmentioning
confidence: 99%
“…KK-A y mice are a congenic strain in which the A y allele at the agouti locus had been transferred to the inbred KK strain by repetitive backcrossing. KK-A y mice are a suitable model of steatohepatitis with metabolic syndrome because they spontaneously become obese and develop hyperglycemia, hyperinsulinemia, and steatohepatitis (28,55,62). We have recently reported that NIAAA model using KK-A y mice exhibits more prominent steatohepatitis than in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%